MARKETING INNOVATIONS IN THE SMES IN BULGARIA AND ICELAND: EMPIRICAL STUDY ON CURRENT SITUATION (International Journal of Innovative Technologies in Economy, 2018)
It is well known that small and medium sized enterprises play a significant role in the economies and especially in smaller countries and in their economies as they reduce unemployment which has a beneficial effect on the social development of societies. The role of innovations as a new and major factor in economic growth continues to be underestimated and this is valid for Bulgaria as well where there is a deficit of research on the innovation activities of the SMEs in Bulgaria. Тhe main goal of this empirical study is to find out the attitude to innovations in SMEs, what kind of innovations related to marketing are conducted by the Bulgarian SMEs - in product design, packaging and marketing communications, what are the differences in the orientation of the business models to innovations. The main data collection method is an online survey with a random sample of SMEs. Part of the empirical data from survey questions are compared with the data from similar research in Iceland provided to the team by the Institute for Innovations Research of Reykjavik University in order to make possible the comparison. According to the survey data there is a difference between the approaches: the Icelandic companies are more inclined to radical innovations while for the Bulgarian companies is more typical the incremental approach to innovations.